Statistical Indicators of the Impact of National Revolution on the Catholic Church in Mexico, 1910–1967 - Wilkie, James Wallace (A journal of church and state, 1970)
James W. Wilkie; Statistical Indicators of the Impact of National Revolution on the Catholic Church in Mexico, 1910–1967, Journal of Church and State, Volume 12